Analysis of Social Structure : A Case Study of Haryana - Indraj, Mr.; Gurjar, Dr. Girdhari Lal; Kumar, Ajay (International Journal of Scientific Research in Civil Engineering, 2018)
In recent times some attention is being paid to the study of social structure and modes of life prevailing in Haryana. This study is also an attempt to study social structure among caste in Haryana society. This paper on Haryana society is studied on the basis of Caste, Class and Power. Caste system is radically different from Caste system in Indian society. The rigid aspect is missing and very few people are ready to attach any importance to ascribed status. In Haryana Class is the base of social structure and most of the times its bases are economic. However, the process of Modernization, secularization, education and new found economic prosperity has made the lines of demarcation very blur and flexibility is quite visible while analyzing social structure in Hindu society.